2021
DOI: 10.1002/asia.202100035
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Simultaneous Synthesis of Circularly Polarized Luminescent Multiple Helicenes Using a Chrysene Framework

Abstract: A series of multiple helicenes was simultaneously synthesized in one step by intramolecular cyclization of a single chrysene derivative containing two 2-[(4-alkoxyphenyl)ethynyl]phenyl units accompanied by rearrangements of the aryl pendants. The electrophile-induced double cyclization with or without aryl migrations proceeded efficiently under acidic conditions to afford annulative p-extension of the chrysene units and produced quadruple (QH-2), triple (TH-2), and double (DH-2) helicenes containing [4]-and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 64 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…through an electrophile-induced intramolecular cyclization accompanied by rearrangements of the aryl pendants. [9,10] During the course of our studies, we found that the introduction of 2,6-dimethyl substituents on the 4-alkoxyphenyl pendants of the cyclization precursor, namely, (R)-1 Me (Figure 2 A), allowed the acid-promoted cyclization to proceed perfectly, without any side reactions probably due to a steric effect, thus quantitatively and chemoselectively producing (R)-2 Me as a single product, as supported by its simple 1 H NMR spectrum (Figure 2 D(iii,iv)). [11] The structure of 2 Me was unambiguously determined by single-crystal X-ray crystallography (Figure 2 C).…”
mentioning
confidence: 99%
“…through an electrophile-induced intramolecular cyclization accompanied by rearrangements of the aryl pendants. [9,10] During the course of our studies, we found that the introduction of 2,6-dimethyl substituents on the 4-alkoxyphenyl pendants of the cyclization precursor, namely, (R)-1 Me (Figure 2 A), allowed the acid-promoted cyclization to proceed perfectly, without any side reactions probably due to a steric effect, thus quantitatively and chemoselectively producing (R)-2 Me as a single product, as supported by its simple 1 H NMR spectrum (Figure 2 D(iii,iv)). [11] The structure of 2 Me was unambiguously determined by single-crystal X-ray crystallography (Figure 2 C).…”
mentioning
confidence: 99%
“…As a result, we, for the first time, succeeded in the perfect diastereospecific synthesis of the homochiral (all‐ P‐ or all‐ M ) consecutively fused double (ExH‐ S ) and triple (ExH‐ M ) expanded helicenes, which were exclusively produced among a number of diastereomers through quantitative and chemoselective acid‐catalyzed diastereospecific multistep cascade cyclizations of the precursors 2 and 3 even composed of a large number of complicated dynamic stereoisomers, respectively (for a multiple helicene synthesis via the gold(I)‐catalyzed cascade cyclizations with moderate to excellent diastereoselectivities, see refs 63, 69, and 70), without any side reactions, including rearrangements of aryl pendants (Figures 2c(i), (iii), (v), and S1). 54,71 The resulting chemoselectivity may arise from the steric effect of the 2,6‐dimethyl substituents on the 4‐alkoxyphenylethynyl pendants 54 . The incorporated expanded helicene subunits in the DFT‐calculated structures of ( M , M )‐ExH‐ S and ( M , M , M )‐ExH‐ M display similar helically twisted conformations with the angles between the two planes of the rings A and K ( θ AK = 28.5–32.1°) and/or those of G and Q ( θ GQ = 26.4°) (Figure 4) that are also comparable to the angle θ AK ( = 25.0 °) of ( M )‐ExH‐ C in the single crystal (Figure 3a(ii)).…”
Section: Resultsmentioning
confidence: 99%
“…TFA‐induced double intramolecular cyclization of chrysene derivatives 27 containing two 2‐[(4‐alkoxyphenyl)ethynyl]phenyl units gave three multiply helicenes simultaneously (quadruple [4]helicene 28 , triple helicene 29 having [4]‐ and [5]helicene frameworks and double [5]helicenes 30 ) in quantitative total yield (Scheme 5). [59] Isolated yields were not high (10, 27 and 10% for 28 a , 29 a and 30 a , respectively).…”
Section: Metal‐free Synthesesmentioning
confidence: 91%